Cooperation in a company: A large-scale experiment - Marvin Deversi; Martin Kocher; Christiane Schwieren (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
We analyze cooperation within a company setting in order to study the relationship between cooperative attitudes and financial as well as non-financial rewards. In total, 910 employees of a large software company participate in an incentivized online experiment. We observe high levels of cooperation and the typical conditional contribution patterns in a modified public goods game. When linking experiment and company record data, we observe that cooperative attitudes of employees do not pay off in terms of financial rewards within the company. Rather, cooperative employees receive non-financial benefits such as recognition or friendship as the main reward medium. In contrast to most studies in the experimental laboratory, sustained levels of cooperation in our company setting relate to non-financial values of cooperation rather than solely to financial incentives.
Keywords: C93; D23; H41; J31; J32; M52; 330; cooperation; social dilemma; field experiment; company